2022
DOI: 10.1136/bmjopen-2022-061749
|View full text |Cite
|
Sign up to set email alerts
|

Interventions delivered in secondary or tertiary medical care settings to improve routine vaccination uptake in children and young people: a scoping review

Abstract: ObjectiveTo identify and analyse the interventions delivered opportunistically in secondary or tertiary medical settings, focused on improving routine vaccination uptake in children and young people.DesignScoping review.Search strategyWe searched CINAHL, Web of Science, Medline, Embase and Cochrane Database of Systematic Reviews for studies in English published between 1989 and 2021 detailing interventions delivered in secondary or tertiary care that aimed to improve childhood vaccination coverage. Title, abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 70 publications
(242 reference statements)
0
6
0
Order By: Relevance
“…However, the vaccinations under investigation, location of presentation within the hospital, and way in which vaccination data were verified, varies considerably. In the previous study,15 for all due/overdue vaccinations (not a measure currently available in England), baseline coverage ranged from 44%16 17 to 89%,18 with little difference by setting and a trend for lower coverage in older studies. For influenza, baseline coverage was lower, ranging from 25%19 to 50.5% 20…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the vaccinations under investigation, location of presentation within the hospital, and way in which vaccination data were verified, varies considerably. In the previous study,15 for all due/overdue vaccinations (not a measure currently available in England), baseline coverage ranged from 44%16 17 to 89%,18 with little difference by setting and a trend for lower coverage in older studies. For influenza, baseline coverage was lower, ranging from 25%19 to 50.5% 20…”
Section: Introductionmentioning
confidence: 87%
“…Previous work to improve vaccination uptake via interventions delivered in secondary or tertiary care (see 15 for overview) has shown that vaccination coverage in CYP attending hospital settings is generally lower than in the general population. However, the vaccinations under investigation, location of presentation within the hospital, and way in which vaccination data were verified, varies considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Children or adults who are unvaccinated or incompletely vaccinated should receive catch‐up polio vaccination. Hospitalists should routinely review the vaccination status of inpatients and offer catch‐up vaccinations in the hospital if feasible, as hospital‐based interventions have been shown to improve routine vaccination rates 13 . In addition, a single lifetime IPV booster can be offered to those in higher‐risk situations, including travel to a polio‐endemic area (or an area with an active polio outbreak), potential occupational exposure to poliovirus (healthcare or laboratory workers who work in an area with active transmission and may encounter poliovirus specimens or patients with poliomyelitis), and contact with individuals with poliomyelitis 12,14…”
Section: Preventionmentioning
confidence: 99%
“…11 to improve routine vaccination rates. 13 In addition, a single lifetime IPV booster can be offered to those in higher-risk situations, including travel to a polio-endemic area (or an area with an active polio outbreak), potential occupational exposure to poliovirus (healthcare or laboratory workers who work in an area with active transmission and may encounter poliovirus specimens or patients with poliomyelitis), and contact with individuals with poliomyelitis. 12,14 Vaccine hesitancy is a persistent threat to poliovirus control, and this problem has been compounded in recent years by both pandemic-related decreases in vaccination coverage and continued use of nonmedical exemptions to vaccine requirements.…”
Section: Preventionmentioning
confidence: 99%
“…The Brazilian National Immunization Program (PNI) was launched in 1973; it is globally acknowledged for its comprehensive vaccination schedule, which covers different life cycles and speci c populations [1;3]. However, reduced vaccination coverage has been observed in the recent global scenario, due to the in uence from factors such as the COVID-19 pandemic, vaccine hesitancy, spread of misinformation about vaccines (Fake news) in social networks, as well as decreased perception about disease-related risks [4][5][6][7][8][9][10][11][12][13]. The World Health Organization (WHO) recommends 95% vaccination coverage for most vaccines to help eradicating, eliminating or controlling immunopreventable diseases [14].…”
Section: Introductionmentioning
confidence: 99%